Novel single nucleotide polymorphism (SNP) interactions within the TG and TSHR gene in a multiplex Malay family with Graves’ disease: A preliminary report - Shahar, Mohammad Arif; Saud Gany, Siti Liyana; Long, Ka Ching; Azizan, Elena; Omar, Ahmad Marzuki; Sukor, Norlela; Kamaruddin, Nor Azmi (Malaysian Endocrine & Metabolic Society, 2016)
Objectives: To identify known single nucleotide polymorphism (SNP) within the TG and TSHR gene in a multiplex Malay family with Graves’ disease Methods: A multiplex family with Graves’ disease was selected for whole exome sequencing. Five family members with Graves’ disease and 4 family members served as control consented to participate in this study. Their clinical history and physical examination were recorded. Fifteen mils of blood were analyzed for thyroid function test, anti-thyroglobulin and antithyroperoxidase antibodies. Deoxyribonucleic acid (DNA) was extracted from 3 mils of whole blood from the subject using Qiagen DNA extraction kit. The DNA was sent to Beijing Genomics Institute (BGI), China, for whole exome sequencing. Illumina Hiseq sequencing platform were used to an average of 100x sequencing depth. The SNP variants were compared with available genomic databases. From all the variants, SNPs within TG gene and TSHR gene were identified and described. Result: Overall, we identified 64,300 SNPs in all individuals. Of these variants, 95.93% were represented in dbSNP and 92.92% were annotated in the 1000 Genomes Project database. The number of novel SNPs was 2,098. Of overall SNPs, 14,325 were synonymous, 13,225 were missense, 37 were stoploss, 109 were stopgain, 23 were startloss and 97 were splice site. We identified 12 known SNP variants within the TG gene (chromosome 8) and 4 known SNP variants within the TSHR gene (chromosome 14). Five of these SNPs are synonymous variants with low impact and 11 SNPs were of missense variants with moderate impact. Both parents and all offspring (i.e normal and affected) carry rs180223, rs2069550, rs853326 SNP variants within the TG gene and rs1991517 SNP variant within the TSHR gene. These SNPs has been previously described to be associated with autoimmune thyroid disorders (AITD). Offspring who are affected carries either rs2076740 and/or rs386495651 within the TG gene from the mother (affected). Interestingly, those with positive thyroid antibodies have rs3783941 variants within the TSHR gene, regardless whether phenotypically they are affected, normal or having subclinical hyperthyroidism. Conclusion: In this Malay multiplex family, parents and offspring carry known SNPs that are associated with AITD. However the presence of rs386495651 and/or rs2076740 within the TG gene and rs3783941within the TSHR gene seems to enhance the effect of known SNPs in producing Graves’ disease and thyroid antibodies positive phenotype. These interactions between SNPs have not been described in AITD before.